Incentivizing Collaborative BIM-Enabled Projects. - Chang, Chen-Yu (Project Management Institute, 2018)
In Incentivizing Collaborative BIM-Enabled Projects: A Synthesis of Agency and Behavioral Approaches, Chen-Yu Chang, PhD, explains the current state of BIM use in three distinct countries: China, the United Kingdom, and the United States. Following multiple case studies in each country, Professor Chang explores the explicit and implicit motivators that may drive BIM participation and the factors that can influence its effectiveness.